Ameliorative Effects of Zataria Multiflora Hydro-Alcoholic extract on Gentamicin Induced Nephrotoxicity in Rats - Hajihashemi, Saeed; Jafarian, Tahereh; Ahmadi, Mahboubeh; Rahbari, Ali; Ghanbari, Fatemeh (Drug Research, 2018)
Background Nephrotoxicity is the major side effects of aminoglycoside antibiotics such as gentamicin. The aim of this study was to investigate the therapeutic effects of Z.multiflora (ZM) hydroalcoholic extract on gentamicin-induced nephrotoxicity.Methods Twenty-eight male Wistar rats categorized into four groups: 1) the control group without injection, 2) the gentamicin treated group (100 mg/kg, i.p) 3) the gentamicin and Z. Multiflora treated group; Z. Multiflora extract(0.8 mg/ml in the drinking water) administered after gentamicin (100 mg/kg, i.p) 4) the normal saline and Z. Multiflora treated group; Z. Multiflora extract (0.8 mg/ml in the drinking water) administered after normal saline injection (2 ml/kg,i.p ).Results Post-treatment with ZM extract caused a significant reduction in the levels of plasma creatinine and blood urea nitrogen (BUN), absolute and fractional excretion of sodium, malondialdehyed (MDA) level in comparison to gentamicin group. In addition, ZM extract significantly increased creatinine clearance, urine osmolarity, and Renal blood flow (RBF) and the Ferric reducing ability of plasma (FRAP) level which had decreased compared to the control group as a result of treatment with gentamicin.Conclusion The above result indicated that ZM extract improved renal toxicity of gentamicin via reducing oxidative stress, oxygen-free radicals, and lipid peroxidation.
Keywords: gentamicin; nephrotoxicity; zataria multiflora; acute renal failure (ARF); rat